Extreme points of L_s(^2l_∞) and P(^2l_∞) - Kim, Sung Guen (Carpathian Mathematical Publications, 2021)
For n≥ 2, we show that every extreme point of the unit ball of L_s(^2l_∞^n) is extreme in L_s(^2l_∞^n+1), which answers the question in [Period. Math. Hungar. 2018, 77 (2), 274-290]. As a corollary we show that every extreme point of the unit ball of L_s(^2l_∞^n) is extreme in L_s(^2l_∞). We also show that every extreme point of the unit ball of P(^2l_∞^2) is extreme in P(^2l_∞^n). As a corollary we show that every extreme point of the unit ball of P(^2l_∞^2) is extreme in P(^2l_∞).